Coloring Pictures as Play Therapy to Reduce Impact of Hospitalization among Children in Hospital - Marfuah, Dewi; Sofiah, Dede Diah (KnE Life Sciences, 2021)
The impact of hospitalization on preschool children may impair the child’s development and healing process. Therefore it is important to minimize the impact of hospitalization. One method to achieve this is by allowing children to play. The purpose of this study was to figure out the effect of therapeutic play (by coloring pictures) on the impact of hospitalization on preschool children in the child care unit of Cibabat-Cimahi Regional Public Hospital, West Java, Indonesia. This was quasi-experimental research with One Group Pre-test Post-test, with a sample of 15 respondents taken by quota sampling. The instrument used was Standard Operating Procedure (SOP) to play coloring pictures and questionnaires on the impact of hospitalization. Coloring pictures was performed once a day (15 minutes / intervention) for 2 days. The data analysis was employed paired with a sample t-test. This research shows the influence of coloring pictures on the impact of hospitalization, with the result of the paired sample t-test statistic shows p value 0.003 (p <0.05). Nurses are expected to be more active in applying coloring pictures to preschool children undergoing hospitalization to reduce the impact of hospitalization. Keywords: Coloring, Hospitalization, Preschool